Study of Vaccination Status and Factors Affecting Health Seeking Behavior of Parents Regarding Immunization - Pankti D Desai; Abidali Y Vijapura (Medsci Publications, 2016)
Introduction: Vaccine preventable diseases are the major causes of morbidity and mortality in children. The study was conducted to find out the proportion of children vaccinated in our hospital and to compare it with various patient variables and to find out the common reasons for incomplete vaccination or non-vaccination. Method: It is a cross sectional study done by interviewing parents of children attending OPD according to preformed questionnaire. Results: 476 (59.5%) children were fully immunized for age, 293 (36.62%) children were partially immunized for age and 31(3.8%) were unimmunized for their age in our study. Proportion of children with BGC vaccination was 94.12% in our study. Proportion of children with primary doses of DPT/Pentavalent with OPV was 82.00%, 72.26% and 63.56% respectively. Conclusion: Non-immunization was inversely proportional to mother's education in our study. There was gradual decline in vaccination with age. The common reasons for not giving vaccines were lack of knowledge (34.56%) and forgetfulness (23.45%). Common sources for vaccination knowledge were vaccination card, advice by nurse or health worker and media. Almost all parents were using mobile phones and were having television.